The Surgical Program in Innovation (SPIN): A Design and Prototyping Curriculum for Surgical Trainees. (September 2021) - Wong, Daniel J.; Miranda-Nieves, David; Nandivada, Prathima; Patel, Madhukar S.; Hashimoto, Daniel A.; Kent, Daniel O.; Gómez-Márquez, José; Lin, Samuel J.; Feldman, Henry J.; Chaikof, Elliot L.
Abstract : Problem: Health professions education does not routinely incorporate training in innovation or creative problem solving. Although some models of innovation education within graduate medical education exist, they often require participants' full-time commitment and removal from clinical training or rely upon participants' existing expertise. There is a need for curricula that teach innovation skills that will enable trainees to identify and solve unmet clinical challenges in everyday practice. To address this gap in surgical graduate education, the authors developed the Surgical Program in Innovation (SPIN). Approach: SPIN, a 6-month workshop-based curriculum, was established in 2016 in the Beth Israel Deaconess Medical Center Department of Surgery to teach surgical trainees the basics of the innovation process, focusing on surgeon-driven problem identification, product design, prototype fabrication, and initial steps in the commercialization process. Participating surgical residents and graduate students attend monthly workshops taught by medical, engineering, and medical technology (MedTech) industry faculty. Participants collaborate in teams to develop a novel device, fabricate a protype, and pitch their product to a panel of judges. Outcomes: From academic years 2015–2016 to 2017–2018, 49 trainees, including 41 surgical residents, participated in SPIN. Across this period, 13 teams identified an unmet need, ideated a solution, and designed and pitched a novel device. Ten teams fabricated prototypes. The 22 SPIN participants who responded to both pre- and postcourse surveys reported significant increases in confidence in generating problem statements, computer-aided design, fabrication of a prototype, and initial commercialization steps (product pitching and business planning). Next Steps: Incorporating innovation education and design thinking into clinical training will prove essential in preparing future physicians to be lifelong problem finders and solvers. The authors plan to expand SPIN to additional clinical specialties, as well as to assess its impact in fostering future innovation and collaboration among program participants. Abstract : Supplemental Digital Content is available in the text.